Biological and social aspects of the theoretical thought of Richard Wallaschek - Muszkalska, Bożena (Interdisciplinary Studies in Musicology, 2018)
The article is devoted to the work of Richard Wallaschek, who was sharply criticised during his lifetime, and only in the 1980s did the academic community renew its interest in his achievements. His book Primitive Music (London 1893) is considered to have laid the foundations for comparative musicology. He sought to prove that comparing European music with the music of primitive peoples was essential, and was the only way to attain a proper view of the products and development of our own culture. The year 1896, in which Wallaschek received his habilitation from the University of Vienna, is regarded as the beginning of comparative musicology in Vienna. Wallaschek postulated that ‘formal aesthetics’, describing merely ‘the chronology of composers’ and marked by an europocentricism, be replaced by a modern musicology, collaborating with music psychology and music ethnography and based on the natural foundations of musical aesthetics - a musicology which would formulate its conclusions on the basis of ‘facts and examples’, which it would verify by means of natural material. A central place in his research was occupied by the genesis of music, musical experiencing and aesthetic judgment, and the perception and creation of music. Taking up the question of musical abilities, Wallaschek devoted much space to women. He considered them more gifted than men, in which he differed from Eduard Hanslick and from other of his contemporary scholars. Postulating a sociological analysis of the situation of musical women in various cultures, he pointed to the methodological necessity of making a strict distinction between the actual musical abilities of women and the social appraisal of those skills.